2000
DOI: 10.1089/end.2000.14.285
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Single-Session Percutaneous Nephrolithotomy: A Feasible and Safe Treatment

Abstract: Bilateral PCNL in a single session is feasible and safe and can be carried out without increased morbidity. We advocate that an endourologist be prepared for bilateral PCNL in the patients in whom it is indicated. The opposite-side PCNL can be done if the first-side treatment is accomplished smoothly and in a reasonable time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 3 publications
1
17
1
1
Order By: Relevance
“…This procedure can be administered in either a staged, synchronous or simultaneous manner (2,7,8). It has been reported that bilateral simultaneous PCNL has some unique advantages such as shorter hospital stay, less radiation exposure, reduced anesthesia and medication requirements, as well as cost-effectiveness (2,7,9). However, the complication rates are similar to bilateral staged or unilateral PCNL (2,10).…”
Section: Discussionmentioning
confidence: 99%
“…This procedure can be administered in either a staged, synchronous or simultaneous manner (2,7,8). It has been reported that bilateral simultaneous PCNL has some unique advantages such as shorter hospital stay, less radiation exposure, reduced anesthesia and medication requirements, as well as cost-effectiveness (2,7,9). However, the complication rates are similar to bilateral staged or unilateral PCNL (2,10).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, decreasing treatment cost and rendering the patient stone free as soon as possible were the driving factors behind our decision to perform bilateral surgery in one session. The efficacy and safety of bilateral simultaneous percutaneous nephrostomy has been demonstrated in the literature [7,8] . Holman et al [9] compared the complications of this procedure with unilateral percutaneous nephrostomy performed in two sessions and found that stone-free rates, renal impairment and the complication rates were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen patients (three girls and 10 boys, 26 kidneys; mean age 8 years, range [3][4][5][6][7][8][9][10][11][12][13][14] underwent simultaneous bilateral percutaneous nephrolithotomy (PCNL) in the same session, under general anaesthesia, starting with ureteric catheter insertion into both kidneys and using a 26 F adult nephroscope. The mean (range) stone diameter was 2 (1-3.5) cm.…”
Section: Methodsmentioning
confidence: 99%
“…This technological advance was slowly applied in children, primarily because of the technical limitations associated with smaller patients and secondly because of the rarity of paediatric urolithiasis. Simultaneous bilateral PCNL (SBPCNL) was reported in adults [1][2][3][4][5][6][7][8]. SBPCNL in children is a challenge for the endourologist; to our knowledge, we report the first series in children.…”
Section: Introductionmentioning
confidence: 99%